140k views
5 votes
Write the statement as an algebraic expression.

The sum of square of c and d increased by twice their product.

User Grapho
by
5.9k points

2 Answers

2 votes

Answer:

c^2+d^2+2cd

Explanation:

Sum= addition

square of c= c^2

square of d= d^2

increased= addition

product= multiplication

twice= 2*

Hope this helps :)

User Dlcardozo
by
4.9k points
4 votes

Answer:


(c^(2)+d)+2(cd)

Explanation:

we know that

The algebraic expression of the phrase " The sum of square of c and d" is equal to adds the square of number c to the number d


(c^(2)+d)

The algebraic expression of the phrase " The sum of square of c and d increased by twice their product" is equal to


(c^(2)+d)+2(cd)

User Catlan
by
4.9k points